CHEMICAL COMPOSITION OF URINARY STONES IN PATIENTS REFERRED TO GEZIRA HOSPITAL FOR RENAL DISEASES AND SURGERY IN GEZIRA STATE CENTRAL SUDAN - Omran, Mustafa; El Imam, Mohammed; Khalid, Khalid Eltahir; Gamar, Sami Yousif; Miskeen, Elhadi (مجلة الجزيرة للعلوم الصحية; مجلد 6 عدد 1 (2010), 2010)
Objective: The purpose of this study was to perform the chemical analysis of stones to know the pattern of biochemical composition of stones in Sudanese subjects. Methods: 169 renal stones were analyzed during the period from February to December 2008. 96 patients were referred to Gezira Hospital for Renal diseases and Surgery (GHRDS), Gezira state, central Sudan. The stones were analyzed by semi quantitative method in the Gezira central laboratory. Kits were used for chemical analysis of stones. Calcium, phosphate, oxalate, uric acid, carbonate and cystine were determined. Results: Male to female ratio was 2:1. Calcium, oxalate and uric acid were the most common forms of stones (90.5%), followed by phosphate (4.7%), carbonate (3.0%) and cystine which accounted for 1.8% of the study subjects. Conclusion: The relative frequency of calcium oxalate stones in our study about 65.1%,outnumbers other types which is compatible with the international literature. While there is relative high percentage of uric acid stones which can be explained by the high animal protein consumption in Sudan together with the hot weather which can be a cause of a highly concentrated urine . Other types phosphates (4.7%), carbonate (3.0%), and cystine which account only ( 1.8%).